Organising a Latin-American anthology in translation under the auspices of the US State Department in the 1940s: Translators and editor’s correspondence - Mitiyo Morinaka, Eliza (Meta, 2023)
Angel Flores, a Puerto Rican literary critic and translator, and Dudley Poore, a North American poet and translator, worked together to compile literary texts from Latin-American countries for the anthology Fiesta in November, published by Houghton Mifflin in 1942. It was part of a translation project subsidised by the US State Department through the Office of the Coordinator of Inter-American Affairs (OCIAA). This article aims to unravel and analyse the process underlying the organisation of Fiesta in November by examining OCIAA documents and Dudley Poore’s unpublished correspondence and by looking into themes such as patronage, manipulation, censorship and policies. It ‘listens’ to the editor’s and translators’ voices to demonstrate the multifaceted practices of an editor and a group of translators, which, in the end, converged and shaped Latin American texts for a US audience under the auspices of the State Department in the 1940s.